Gross efficiency during flat and uphill cycling in field conditions - Nimmerichter, A.; Prinz, B.; Haselsberger, K.; Novak, N.; Simon, D.; Hopker, J. G. (International Journal of Sports Physiology and Performance, 2015)
Purpose: While a number of studies have investigated gross efficiency (GE) in laboratory conditions, few studies have analyzed it in field conditions. Therefore, the aim of this study was to analyze the effect of gradient and cadence on GE in field conditions. Methods: Thirteen trained cyclists (mean ± SD age 23.3 ± 4.1 y, stature 177.0 ± 5.5 cm, body mass 69.0 ± 7.2 kg, maximal oxygen uptake [VO2max] 68.4 ± 5.1 mL · min-1 · kg-1) completed an incremental graded exercise test to determine ventilatory threshold (VT) and 4 field trials of 6 min duration at 90% of VT on flat (1.1%) and uphill terrain (5.1%) with 2 different cadences (60 and 90 rpm). VO2 was measured with a portable gas analyzer and power output was controlled with a mobile power crank that was mounted on a 26-in mountain bike. Results: GE was significantly affected by cadence (20.6% ± 1.7% vs 18.1% ± 1.3% at 60 and 90 rpm, respectively; P < .001) and terrain (20.0% ± 1.5% vs 18.7% ± 1.7% at flat and uphill cycling, respectively; P = .029). The end-exercise VO2 was 2536 ± 352 and 2594 ± 329 mL/min for flat and uphill cycling, respectively (P = .489). There was a significant difference in end-exercise VO2 between 60 (2352 ± 193 mL/min) and 90 rpm (2778 ± 431 mL/min) (P < .001). Conclusion: These findings support previous laboratory-based studies demonstrating reductions in GE with increasing cadence and gradient that might be attributed to changes in muscle-activity pattern.